Dimensi Nilai dan Pembelajaran Etika dalam Konsep Murabahah Perspektif Tafsir al-Azhar - Juliana Putri; Dicky Armanda; Muhammad Syahrial Razali Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the dominant use of the murabahah contract in contemporary Islamic economic practices, which is often understood in a technical-formal manner, thus potentially obscuring the value dimensions and ethical learning contained therein. This study aims to analyze the value dimensions and ethical learning in the murabahah concept based on the verses of the Qur'an on trade and usury and their interpretation in Buya Hamka's Tafsir al-Azhar. The research method used is qualitative with a library research design and a normative-interpretative approach, with data sources consisting of the Qur'an, Tafsir al-Azhar, and scientific literature related to Islamic economics and the ethics of muamalah. The results of the discussion indicate that murabahah obtains Qur'anic legitimacy because it is based on a fair, transparent, and exchange-based buying and selling mechanism based on real benefits, which is fundamentally different from usury which is exploitative. The research findings confirm that according to Buya Hamka, murabahah is not only an economic contract, but also a medium for internalizing Islamic educational values ​​that instill honesty, justice, trustworthiness, and social responsibility, and will lose its ethical meaning if carried out formally. The implications of this research indicate that strengthening murabahah practices requires integration between legal compliance and value awareness, so that murabahah can function as an educational instrument for Islamic economic ethics that is in line with the objectives of sharia (maqāṣid al-sharī‘ah) and contemporary social needs.